Analysis of Radiation Efficiency of Microstrip Dipole Antenna Based on Cohen-Minkowski Fractal - Bhima Andika Putra; Muhammad Erpandi Dalimunthe; Beni Satria (Sean Institute, 2025)
The performance of microstrip antennas can be significantly improved through fractal geometry, particularly in achieving size reduction and multiband behavior. This study investigates the radiation efficiency of a microstrip dipole antenna employing the Cohen-Minkowski fractal geometry. The antenna is designed using FR4 substrate material with a dielectric constant of 4.4 and is simulated in multiple fractal iterations. Simulations are conducted using CST Studio Suite to observe return loss (S11), gain, and radiation efficiency across different frequencies. The results show that the incorporation of Cohen-Minkowski geometry increases surface current path length, enabling better impedance matching and improved radiation efficiency, especially at higher iterations.